Marketing Strategy for Small- to Medium-Sized Manufacturers - France, Charles E (Business Expert Press, 2013)
Ebook from IG Library ; Does this sound familiar? You've tried to grow your business but have produced less-than-desired results. You've learned that your working capital, cash flow, financial ratios, and overall profitability are insufficient to afford the costs of needed sales, marketing, and promotional strategies typically called for to find and develop new customers, markets, and products. It's very common that company executives do not follow generally accepted basic business practices such as knowing product costs and margins, obtaining strategically useful information about customers, conducting market research to identify prospective customers, and understanding competitors' advantages and disadvantages needed to build effective growth strategies. Based on 21 case studies and 126 reviews of manufacturers' sales and marketing practices, this book explains the common pitfalls so many companies experience, and it offers common sense, practicable, and affordable step-by-step 'how to's' for cost and profitability analyses on products and customers. It will help you find prospective new customers, conduct smart market research, and decipher and use competitor intelligence. It also provides guidelines for determining the best combination of sales coverage for inside/outside sales and independent reps and for estimating the cost to implement sales, marketing, promotional, and growth strategies.